A high-resolution multiband survey of Westerlund 2 with the Hubble Space Telescope: II. Mass accretion in the pre-main sequence population - Zeidler, Peter; Grebel, Eva K.; Pasquali, Anna (Arxiv, 2016)
We present a detailed analysis of the pre-main-sequence (PMS) population of the young star cluster Westerlund~2 (Wd2), the central ionizing cluster of the HII region RCW 49, using data from a high resolution multi-band survey with the Hubble Space Telescope. The data were acquired with the Advanced Camera for Surveys in the F555W, F814W, and F658N filters and with the Wide Field Camera 3 in the F125W, F160W, and F128N filters. We find a mean age of the region of 1.04+-0.72 Myr. The combination of dereddened F555W and F814W photometry in combination with F658N photometry allows us to study and identify stars with H_alpha excess emission. With a careful selection of 240 bona-fide PMS H_alpha excess emitters we were able to determine their H_alpha luminosity, which has a mean value L(H_alpha)=1.67 x 10^{-31} erg s^{-1}. Using the PARSEC 1.2S isochrones to obtain the stellar parameters of the PMS stars we determined a mean mass accretion rate \dot M_acc=4.43 x 10^{-8} M_sun yr^{-1} per star. A careful analysis of the spatial dependence of the mass-accretion rate suggests that this rate is ~25% lower in center of the two density peaks of Wd2 in close proximity to the luminous OB stars, compared to the Wd2 average. This rate is higher with increasing distance from the OB stars, indicating that the PMS accretion disks are being rapidly destroyed by the far-ultra-violet radiation emitted by the OB population.
Gesehen am 06.11.2017